2021
DOI: 10.48550/arxiv.2112.08149
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robust topological superconductivity in weakly coupled nanowire-superconductor hybrid structures

Oladunjoye A. Awoga,
Jorge Cayao,
Annica M. Black-Schaffer

Abstract: We investigate the role of the coupling between a spin-orbit coupled semiconductor nanowire and a conventional s-wave superconductor on the emergence of the topological superconducting phase with Majorana bound states in an applied magnetic field. We show that when the coupling is strong, the topological phase transition point is very sensitive to the size of the superconductor and in order to reach the topological phase a strong magnetic field is required, which can easily be detrimental for superconductivity… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…1 where the TI nanowire is strongly tunnel coupled to a thin layer (∼10 nm) of superconductor. In semiconductors that possess strong Rashba spin-orbit coupling-which have also been predicted to host MBSs in certain circumstances [34,35]-the full influence of the tunnel coupling to a superconducting layer has previously been analyzed [36][37][38][39][40][41][42][43] and revealed that a significant roadblock to achieving MBSs in semiconductors is the metallization of the semiconductor by the superconductor. Metallization [37,38] is the process by which, when a large pairing potential is induced in the semiconductor, other properties of the semiconductor are renormalized toward the values of the attached superconducting metal.…”
Section: Introductionmentioning
confidence: 99%
“…1 where the TI nanowire is strongly tunnel coupled to a thin layer (∼10 nm) of superconductor. In semiconductors that possess strong Rashba spin-orbit coupling-which have also been predicted to host MBSs in certain circumstances [34,35]-the full influence of the tunnel coupling to a superconducting layer has previously been analyzed [36][37][38][39][40][41][42][43] and revealed that a significant roadblock to achieving MBSs in semiconductors is the metallization of the semiconductor by the superconductor. Metallization [37,38] is the process by which, when a large pairing potential is induced in the semiconductor, other properties of the semiconductor are renormalized toward the values of the attached superconducting metal.…”
Section: Introductionmentioning
confidence: 99%